Optimizing Outcomes following Total and Subtotal Tongue Reconstruction: A Systematic Review of the Contemporary Literature - Manrique, Oscar J.; Leland, Hyuma A.; Langevin, Claude-Jean; Wong, Alex; Carey, Joseph N.; Ciudad, Pedro; Chen, Hung-Chi; Patel, Ketan M. (Journal of Reconstructive Microsurgery, 2017)
Background More than 45,000 Americans are diagnosed with oropharyngeal cancer annually and multimodal treatment often requires wide excision, lymphadenectomy, chemotherapy, and radiation. Total and subtotal lingual resection severely impairs speech, swallow, and quality of life (QoL). This study investigates functional outcomes and QoL following subtotal and total tongue resection with free tissue transfer reconstruction.Materials and Methods A systematic review of the English language literature was performed using PubMed, Ovid, Embase, and Cochrane databases based on predetermined inclusion/exclusion criteria. Included studies were reviewed for surgical technique, adjuvant treatment, surgical and functional outcomes, and QoL.Results From an initial search yield of 1,467 articles, 22 studies were included for final analysis. Speech intelligibility was correlated with the volume and degree of protuberance of the neotongue. Adjuvant therapy (radiation) and large tumor size were associated with worse speech and swallow recovery. At 1 year follow-up, despite 14 to 20% rates of silent aspiration, 82 to 97% of patients resumed oral feeding. Neurotized flaps have been demonstrated to improve flap sensation but have not yet demonstrated any significant impact on speech or swallow recovery. Finally, many patients continue to experience pain after surgery, but patient motivation, family support with physician, and speech therapist follow-up are associated with improved QoL scores.Conclusion Tongue reconstruction is dictated by the amount of soft tissue resection. Taking into consideration the most common factors involved after tongue resection and reconstruction, further studies should focus on more objective measurements to offer solutions and maximize final outcomes.
Keywords: tongue cancer; tongue reconstruction; outcomes